Dynamics of cognitive business models of enterprises in the digital economy - Jabłoński, Marek; Jabłoński, Adam; Szpitter, Agnieszka Anna (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
Digital transformation creates new perspectives for the development of business models. The result of this process is the emergence of new ways of monetizing them. This creates a new dimension in achieving high efficiency for enterprises operating in the digital ecosystem. The changing business logic opens the way to creating new business models and their further evolution. In this context, digital business models are transforming into their higher stage of development becoming cognitive business models. Cognitive business models are based on new learning algorithms supported by multidimensional business analytics and dynamic inference with strong customer involvement. This can be achieved by introducing dynamics to digital business models, accelerating their further exploration and exploitation, including flexible intelligent solutions embedded in services. Then new and intelligent ways of delivering value appear. Monetization is a factor that stimulates the dynamics of business models. Monetization schemes strongly influence the attractiveness of digital business models. The aim of the article is to present the results of bibliographic research used to identify and characterize key determinants responsible for the dynamics of business models functioning in the digital environment. The scope of the article includes the principles of design and implementation of business models embedded in the digital ecosystem in the context of various monetization schemes.